The Interactive Role of Green Knowledge Acquisition In The Relationship Between Green Learning And Environmental Resilience: An Applied Study of The Opinions of A Sample of Employees At Al-Kafeel Meat Production Company - Ameera Ajel (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The current research aims to identify the interactive role of acquiring green knowledge in the relationship between green learning with its dimensions (cognitive, skill-based, organisational, technological) and sustainable resilience with its dimensions (economic sustainability, social sustainability, environmental sustainability). It is an applied study based on the opinions of a sample of 132 employees from Al-Kafeel Meat Production Company. The research problem was represented by the main question: "What is the interactive role of acquiring green knowledge in the relationship between green learning and environmental resilience?" The questionnaire was used as the main tool for data collection, and statistical programs (AMOS.V.29, SPSS.V.29) were employed. The research results indicated that a higher level of green learning among employees contributes to enhancing the organization's ability to adapt to environmental changes and improving its environmental resilience.